Immune Defects in the Risk of Infection and Response to Vaccination in Monoclonal Gammopathy of Undetermined Significance and Multiple Myeloma - Tete, Sarah M.; Bijl, Marc; Sahota, Surinder S.; Bos, Nicolaas A. (Frontiers in Immunology, 2014)
The plasma cell proliferative disorders monoclonal gammopathy of undetermined significance (MGUS) and malignant multiple myeloma (MM) are characterized by an accumulation of transformed clonal plasma cells in the bone marrow and production of monoclonal immunoglobulin. They typically affect an older population, with median age of diagnosis of approximately 70 years. In both disorders, there is an increased risk of infection due to the immunosuppressive effects of disease and conjointly of therapy in MM, and response to vaccination to counter infection is compromised. The underlying factors in a weakened immune response in MGUS and MM are as yet not fully understood. A confounding factor is the onset of normal aging, which quantitatively and qualitatively hampers humoral immunity to affect response to infection and vaccination. In this review, we examine the status of immune alterations in MGUS and MM and set these against normal aging immune responses. We focus primarily on quantitative and functional aspects of B-cell immunity. Furthermore, we review the current knowledge relating to susceptibility to infectious disease in MGUS and MM, and how efficacy of conventional vaccination is affected by proliferative disease-related and therapy-related factors.